Immunogenic Targets for Specific Immunotherapy in Multiple Myeloma. (7th May 2012) - Zhang, Lu; Götz, Marlies; Hofmann, Susanne; Greiner, Jochen
Abstract : Multiple myeloma remains an incurable disease although the prognosis has been improved by novel therapeutics and agents recently. Relapse occurs in the majority of patients and becomes fatal finally. Immunotherapy might be a powerful intervention to maintain a long-lasting control of minimal residual disease or to even eradicate disseminated tumor cells. Several tumor-associated antigens have been identified in patients with multiple myeloma. These antigens are expressed in a tumor-specific or tumor-restricted pattern, are able to elicit immune response, and thus could serve as targets for immunotherapy. This review discusses immunogenic antigens with therapeutic potential for multiple myeloma.